2021
DOI: 10.3389/fmed.2021.717194
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Sequelae of COVID-19 Nearly 1 Year After Diagnosis

Abstract: Background: A previous study has shown that 81% of the COVID-19 patients had mild or moderate symptoms. However, most studies on the sequelae in COVID-19 patients focused on severe cases and the long-term follow-up studies on the health consequences in non-severe cases are limited. The current study aimed to assess the sequelae of COVID-19 in patients nearly 1 year after diagnosis with a particular focus on the recovery of patients with non-severe COVID-19.Methods: We enrolled 120 patients infected with SARS-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
93
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(114 citation statements)
references
References 33 publications
12
93
1
Order By: Relevance
“…Among the 193 studies under full-text review, 153 studies were excluded. Eventually, 40 studies were included in this meta-analysis based on the inclusion criteria [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. The literature retrieval flow chart is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the 193 studies under full-text review, 153 studies were excluded. Eventually, 40 studies were included in this meta-analysis based on the inclusion criteria [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. The literature retrieval flow chart is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Mental health disorders after acute COVID-19, including mainly anxiety, depression, and PTSD, have attracted widespread attention, but the prevalence varies widely among studies. 7 , 37 , 38 , 39 , 40 , 41 , 42 , 43 Mental health problems after COVID-19 might be attributed to the direct effects of SARS-CoV-2 infection, isolation, physical distancing, incomplete recovery of physical health, and financial difficulties. 26 , 44 An encouraging finding of our study was that the proportion of participants with anxiety or depression gradually decreased throughout the 2 years, regardless of initial disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Different assessment methods for mental health might partly explain the huge variation in the prevalence of mental health disorders after COVID-19 in previous studies. 7 , 37 , 38 , 39 , 40 , 41 , 42 , 43 In fact, due to the high heterogeneity of follow-up studies of COVID-19, differences were also observed in long COVID prevalence and obscured our understanding of it. 26 Hence, there is an urgent need to develop norms to reduce heterogeneity among studies, such as core outcome sets (especially for symptoms requiring priority evaluation), validated assessment tools, broadly recognised symptom questionnaires, and specific follow-up timepoints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4% Loss of appetite 1-9% # Reference: [27] $ Reference: [25] § Reference: [28,29,[123][124][125] J o u r n a l P r e -p r o o f J o u r n a l P r e -p r o o f…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%